How Factors of the Interpretive Structural Model Affect the Intent to Buy Original Brand Soccer Balls? - Hasan Gholami Ghajari; Masoumeh Kalateh Seifari (The Society of Aging and Physical Activity (SAPA), 2017)
Background. A soccer ball is the principal piece of sports equipment for soccer and original brands compete with each other for a big pie of the market. Objectives. The aim of this study's interpretive structural model (ISM) was to ascertain the factors that affect the intent to purchase original brand soccer balls. Methods. First, by a study of the literature and by the use of the Delphi technique, effective factors impacting the intent to buy original brand soccer balls were identified. The ISM was then drawn up to show factors affecting the intent to buy an original brand soccer ball. The study's population consisted of the country's sports management professors as samples and eight experts were chosen in a targeted manner. The MATLAB2014 software was used for the implementation of the ISM. Results. The findings were shown in diagrams with five levels. The factor 'ball appearance' was at the fifth level, the factors 'brand name' and 'country of manufacturer of brand' was at the fourth level, 'congruence of price and quality' was at the third level, four factors of 'brand identity', 'brand image', 'perceived value', and 'brand store sales' were at the second level, and 'intention to buy' was at the first level. Conclusion. An original brand soccer ball should be beautiful and have an attractive design. It must have a proper shape and it must create a unique identity so that the positive image of the product is accepted by customers. It must create value for customers when they weigh two aspects: What they have paid for it and what they have received.